A Study on the Prevention of Cracks on the Trepan Area of Motor Bearing - Lee, Kyung Won; Ban, Jae Sam; Kang, Heyong Seon; Cho, Kyu Zong (Journal of mechanical science and technology, 2003)
Trepan prevents the wear of the inside part of a bearing when the initial shaft rotates. It continuously contacts with the eccentric part of the shaft in rotation and is loaded repeatedly. Therefore, even if an early crack of a trepan part is small, the crack may progress by the repeated load. If the crack progresses, very small chips come out. This is put in the rotor and prevents the rotation of the compressor. There can be leaks in a microgroove and extreme wear can occur due to lack of oil on the surface contact part. Therefore, this study was carried out to compare and investigate the trepan strength and deflection characteristics between trepan locations and dimension changes using the finite element method and search a motor bearing for a model with bigger stiffness of a trepan part and the same deflection.